2018
DOI: 10.1016/j.jfluidstructs.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of the behaviour and performance of ships advancing through restricted shallow waters

Abstract: Upon entering shallow waters, ships experience a number of changes due to the hydrodynamic interaction between the hull and the seabed. Some of these changes are expressed in a pronounced increase in sinkage, trim and resistance. In this paper, a numerical study is performed on the Duisburg Test Case (DTC) container ship using Computational Fluid Dynamics (CFD), the Slender-Body theory and various empirical methods. A parametric comparison of the behaviour and performance estimation techniques in shallow water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 30 publications
1
50
0
Order By: Relevance
“…The Grid Convergence Index (GCI) method based on Richardson's extrapolation [28] was used to estimate the numerical uncertainties. It is of note that, although the GCI method was firstly proposed for spatial convergence studies, it can also be used for a temporal convergence study, as similarly used by Tezdogan et al [29] and Terziev et al [30].…”
Section: Verificationmentioning
confidence: 99%
“…The Grid Convergence Index (GCI) method based on Richardson's extrapolation [28] was used to estimate the numerical uncertainties. It is of note that, although the GCI method was firstly proposed for spatial convergence studies, it can also be used for a temporal convergence study, as similarly used by Tezdogan et al [29] and Terziev et al [30].…”
Section: Verificationmentioning
confidence: 99%
“…Observations on Figure 15 may also help to explain the model behaviour at that speed and blockage ratio. Terziev, et al (2018) presented a numerical study on the DTC container ship in shallow water in order to investigate the sinkage, trim and resistance of ships advancing through restricted shallow water in varying channel cross sections and ship speeds. The authors used Computational Fluid Dynamics (CFD), the Slender-Body theory and various empirical methods to calculate the trim and squat of a containership advancing through different channel geometries.…”
Section: Fnhmentioning
confidence: 99%
“…The indirect methods have been preferred by researchers to the direct methods since the indirect methods are generally simpler and more economical compare to the direct methods. Accordingly, there have been a large number of experimental studies to acquire roughness functions and the corresponding roughness Reynolds number, + , using the indirect methods derived by Granville (1958;1982;1987), including local method with displacement thickness (Schultz and Swain, 1999;Flack et al, 2005;Schultz et al, 2015), local method without displacement thickness (Karlsson, 1978), overall method (Schultz and Myers, 2003;Schultz, 2004;Shapiro, 2004;Demirel, 2015;Demirel et al 2017a) or rotating disk method (Schultz and Myers, 2003;Holm et al, 2004). Schultz and Myers (2003) further concluded that the roughness functions obtained from the different indirect methods can bring a good agreement with the results obtained from the direct method.…”
Section: Introductionmentioning
confidence: 99%